Islam, Pluralisme, Dan Tantangan Moderasi Beragama Di Indonesia: Sebuah Kajian Sosio-Religius - Hadi Suprapto (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
Religious moderation has become an important discourse in maintaining social harmony within Indonesia's multicultural and multireligious society. This article examines the challenges and strategies in fostering moderate religious attitudes through a multicultural and multireligious counseling approach in the educational environment. The research was conducted using a literature review method that examined various literature related to education, counseling, and diversity. The study results indicate that religious moderation has not been optimally implemented, particularly in the education curriculum, which tends to focus on cognitive aspects. The multicultural-based counseling approach is considered effective in fostering pluralistic awareness, as it allows for the internalization of values of tolerance, justice, and openness. Counselors are required to possess multicultural awareness, knowledge, and skills in order to guide students contextually according to their cultural and religious backgrounds. In this context, education becomes a strategic medium to instill values of moderation and shape the inclusive character of students. Therefore, there is a need for the integration of pluralism and inclusivity values in the educational process more comprehensively to minimize conflicts and religion-based radicalism.